2022
DOI: 10.3390/vetsci9040154
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and Molecular Epidemiology of Fowl Adenovirus Serotype 4 Outbreaks in Broiler Chicken in Abu Dhabi Emirate, UAE

Abstract: Background: Fowl adenovirus serotype 4 (FAdV-4), causing inclusion body hepatitis (IBH) and hydropericardium hepatitis syndrome (HPS), is responsible for the significant economic losses in poultry industry worldwide. This study describes FAdV disease and molecular characteristics of the virus as the first report in UAE. Methodology: Clinical, necropsy, histopathology, qPCR and phylogenetic analysis of hexon gene were used to diagnose and characterize the virus. Results: The age of the infected broiler chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…In addition, several reports of IBH and/or HHS were documented in Japan ( 31 ), Korea ( 32 ), India ( 33 ), Pakistan ( 34 ), Spain ( 25 ), Poland ( 35 ), Iran ( 36 ), Mexico ( 37 ), Brazil ( 38 ), Croatia ( 39 ), Australia ( 40 ), Greece ( 41 ), Iraq ( 42 ), Palastine ( 43 ), United Arab Emirates ( 44 ), Saudi Arabia ( 45 ), Morocco ( 46 ), and South Africa ( 47 ).…”
Section: Current Status Of Ibh And/or Hhs Associated Problemsmentioning
confidence: 99%
“…In addition, several reports of IBH and/or HHS were documented in Japan ( 31 ), Korea ( 32 ), India ( 33 ), Pakistan ( 34 ), Spain ( 25 ), Poland ( 35 ), Iran ( 36 ), Mexico ( 37 ), Brazil ( 38 ), Croatia ( 39 ), Australia ( 40 ), Greece ( 41 ), Iraq ( 42 ), Palastine ( 43 ), United Arab Emirates ( 44 ), Saudi Arabia ( 45 ), Morocco ( 46 ), and South Africa ( 47 ).…”
Section: Current Status Of Ibh And/or Hhs Associated Problemsmentioning
confidence: 99%
“…On the other hand, the birds analyzed in this study were not vaccinated, so it can be deduced that the viral strains that are present in commercial batches are field strains. Many studies showed that the genotypes characterized here were associated with outbreaks of IBH or HHS in chickens in several countries around the world [ 41 , 46 , 47 , 48 ]; however, the vast majority of reports of IBH or HHS worldwide have been associated with FAdV-4/C1 [ 23 , 49 , 50 , 51 , 52 ] and the report of a large number of outbreaks associated with this FAdV genotype has led many studies to focus on the development of vaccines based on this viral genotype [ 53 , 54 , 55 ], as well as associations with other genotypes (FAdV-8b/E3) where excellent protection against infections with both genotypes is shown [ 1 , 12 , 56 , 57 , 58 ]. However, these recombinant vaccines have not been tested with other FAdV genotypes that are included in the same group to which the vaccine strains belong, in the case of FAdV-8b/E3 belonging to species E, perhaps it could generate protection against FAdV-8a/E2 and FAdV-6/E1 strains and be an alternative in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Hydropericardium hepatitis syndrome (HHS), formerly called hydropericardium syndrome (HPS) and Angara disease, was first described in 1987 in broiler chickens in Angara Goth, Pakistan [3]. Since 2015, after the detection of hypervirulent strain of FAdV-4 in China [32,38] HHS cases have increased and severe outbreaks of HHS have been reported in chicken flocks in many countries like Iran, India, China, Egypt, United Arab Emirates, Poland and USA causing economical losses especially in 3-5 weeks old broilers with mortality rate up to 100% [6][7][8][9][10][11][12][13][14][15][16][17]. After the report of hypervirulent FAdV-4 strain and its rapid spread in China [32,38] the emergent novel FAdV-4 serotype became very important virus to investigate in terms of molecular epidemiology and vaccine design.…”
Section: Discussionmentioning
confidence: 99%
“…FAdVs are transmitted vertically and horizontally via all excretions, but the highest titers are found in feces and therefore fecal-oral transmission is very efficient way of transmission [19]. Because of rapid spread via feces and emergence of hypervirulent strain in China, outbreaks have been reported in the Middle east, Africa, Asia and recently in the USA [8][9][10][11][12][13][14][15][16][17]. However, there is no report about the occurrence of this disease complex in Azerbaijan at present.…”
Section: Of 22mentioning
confidence: 99%